ANALYSIS OF GRAIN YIELD FROM A LONG-TERM EXPERIMENT ON INTEGRATED NUTRIENT MANAGEMENT IN SORGHUM-WHEAT CROPPING SYSTEM - SHARMA, V.K.; KAUR, RAJINDER; TOMAR, R.S (Annals of Agricultural Research, 2014)
Grain yield data from a long-term experiment on integrated nutrient management in sorghumwheat cropping sequence conducted during 1984-85 to 2002-03 at Akola centre have been analyzed. Analysis revealed that year, treatment and replication effects were highly significant and so were the two-factor interactions except the treatment x replication interaction. The treatment with 50% recommended NPK dose through fertilizers + 50% N through farmyard manure in kharif and 100% recommended NPK dose through fertilizers in rabi came out to be the best treatment for the centre in terms of giving highest grain yield for both the crops together. However, a declining trend in the yield of both the crops was observed under this treatment. Moreover, high amount of rainfall had yield depressing effect on sorghum and wheat and increased number of fallow days adversely affected the sorghum yield. The number of irrigations had positive effect on the yield of wheat crop.